Recovery among post-arrest patients with mild-to-moderate cerebral edema - Fuller, Zachary L. (Resuscitation, 2021)
BACKGROUND: Cerebral edema after cardiac arrest may be a modifiable cause of secondary brain injury. We aimed to identify processes of care associated with recovery in a cohort of patients with mild to moderate edema. METHODS: We conducted a retrospective cohort study of adults resuscitated from out-of-hospital arrest (OHCA) at a single center from 2010–2018. We included those with cerebral edema ranging from mild to moderate (gray to white matter attenuation ratio (GWR) 1.2 to 1.3 on initial brain computerized tomography (CT). We used Pittsburgh Cardiac Arrest Category (PCAC) to adjust for illness severity and considered the following values in the first 24 hours of admission as additional predictors: GWR, lab values affecting serum osmolality (sodium, glucose, blood urea nitrogen (BUN)), total osmolality, change in osmolality from 0 to 24 hours, cardiac etiology of arrest, targeted temperature to 33°C (vs 36°C), time-weighted mean arterial pressure (MAP), partial pressures of arterial oxygen and carbon dioxide and select medications. Our primary outcome was discharge with Cerebral Performance Category 1 to 3. We used unadjusted and adjusted logistic regression for analysis. RESULTS: We included 214 patients for whom CT was performed median 3.8 [IQR 2.4 – 5.2] hours after collapse. Median age was 57 [IQR 48–67] years, 82 (38%) were female, and 68 (32%) arrested from ventricular tachycardia or fibrillation. In adjusted models, modifiable processes of care were not associated with outcome. CONCLUSIONS: Illness severity, but not modifiable processes of care, were associated with recovery among post-arrest patients with mild-to-moderate cerebral edema.